BETA DAN IMPLIKASINYA TERHADAP HASIL DIVERSIFIKASI SAHAM DI BURSA EFEK JAKARTA - Novalina Taliawo; Dorkas Rambu Atahau (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2007)
According to portfolio theory, diversification is a way to reduce unsystematic- risk. The more assets we put in our portfolio, the less unsystematic risk we have. By doing this the only risk left in the portfolio that should be considered by investors is the systematic risk which is measured by beta. The objective of this research is to obtain an empirical evidence on the speed of reduction in portfolio’s beta by comparing portfolio that consists of high- beta assets and low- beta assets. The result shows that portfolio consists of low beta assets have a higher speed in reducing the systematic risk compare to portfolio consist of high beta assets. It implies the needs to consider the magnitude of an asset beta in constructing a portfolio to reduce portfolio systematic risk. Keywords : Portfolio, beta, systematic risk, unsystematic risk